The influence of socio-cultural factors on the performance of female entrepreneurs - Gogo Rachael Adiza; Ule Prince Alamina; Idemudia Sunday Aliyu (Goodwood Publishing, 2020)
Purpose: The potential contribution of female entrepreneurial activities geared towards the growth and development of economies cannot be neglected despite the numerous challenges faced by women as a result of cultural practices. The study investigated the influence of socio-cultural factors on the performance of female entrepreneurs. Research methodology: A cross sectional survey design was utilized to obtain 160 female entrepreneurs from four Niger Delta States. Data collected using convenience sampling techniques and analyzed with multiple regression. Result: The outcome revealed that socio-cultural dimensions influenced female entrepreneurial performance at varying degrees hence; it was concluded that since individuals do not live in a vacuum but social context, there is the tendency of cultural factors influencing their behaviours towards business venturing which is the burning desires to gain self recognition and social mobility. Limitations: The greatest challenge was the researchers’ inability to cover the nine Niger Delta States. Contribution: The study advocated for women education which would equip them with the requisite knowledge to challenge some of the cultural excesses in the region as most men still live in the past by bringing obsolete ideas that infuses negative attitude towards female entrepreneurial engagement in the region. Keywords: Attitude towards risk-taking, Attitude towards wealth gains, Attitude towards innovation, Push and pull motivations